Identifying green spaces in Kuala Lumpur using higher resolution satellite imagery - Mohd Yusof, Mohd Johari (Faculty of Design & Architecture, Universiti Putra Malaysia, 2012)
There is a growing need for municipal councils to map and to monitor the extent and condition of urban green spaces, as one measure of the overall sustainability of a city. In this study, we identify the information about urban green spaces that can be obtained from satellite imagery. This research which is based in the city of Kuala Lumpur tests the ability of IKONOS higher resolution satellite imagery in identifying the different types and the different functions provided by green spaces using both automated methods and manual methods of visual interpretation. Both these methods were found to produce a map of green space for the entire city area that was 70% accurate when validated against ground surveys. In cases where higher resolution satellite imagery exists, we show how it can produce a variety of enhanced information which may enable city planners to monitor green space more regularly and to evaluate consistently which areas of green space within the city ought to be protected in order to maintain its benefits for the city population